Basic principles and calculations in chemical engineering - Himmelblau, David M.; Riggs, James B. (Boston Pearson Education Ltd., 2024)
"Basic Principles and Calculations in Chemical Engineering, Ninth Edition, has been thoroughly revised, streamlined, and updated to reflect sweeping changes in the chemical engineering field. This introductory guide addresses the full scope of contemporary chemical, petroleum, and environmental engineering applications and contains extensive new coverage and examples related to biotech, nanotech, green/environmental engineering, and process safety, with many new MATLAB and Python problems throughout. Authors David M. Himmelblau and James B. Riggs offer a strong foundation of skills and knowledge for successful study and practice, guiding students through formulating and solving material and energy balance problems, as well as describing gases, liquids, and vapors. Throughout, they introduce efficient, consistent, learner-friendly ways to solve problems, analyze data, and gain a conceptual, application-based understanding of modern processes. This edition condenses coverage from previous editions to serve today's students and faculty more efficiently. In two entirely new chapters, the authors provide a comprehensive introduction to dynamic material and energy balances, as well as psychrometric charts"--
Catalography